2003
DOI: 10.1128/mcb.23.5.1737-1749.2003
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Recognition of Nonconsensus AP-1 Sites by Fos-Jun and Jun-Jun Influences Transcriptional Cooperativity with NFAT1

Abstract: The recognition sequences for individual transcription regulatory proteins vary among different promoter regions. The reasons for this diversity of recognition sequences are not well understood. The recognition sequences are frequently suboptimal binding sites for the regulatory proteins, which would appear to impede the already formidable task of transcription factors: to specify unique sites of transcription initiation in the genome. In some cases, replacement of nonconsensus recognition sequences by optimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 46 publications
2
24
0
1
Order By: Relevance
“…Additional studies have shown that nonconsensus AP-1 sites may be functionally active. Their sequence composition may influence the cooperation of AP-1 with other transcription factors and thus the transcriptional activity (40). Furthermore, it can be assumed that lower-affinity binding is a crucial prerequisite for AP-1 displacement by adjacent binding factors, as observed here for the HPV8 E2 protein.…”
Section: Discussionmentioning
confidence: 76%
“…Additional studies have shown that nonconsensus AP-1 sites may be functionally active. Their sequence composition may influence the cooperation of AP-1 with other transcription factors and thus the transcriptional activity (40). Furthermore, it can be assumed that lower-affinity binding is a crucial prerequisite for AP-1 displacement by adjacent binding factors, as observed here for the HPV8 E2 protein.…”
Section: Discussionmentioning
confidence: 76%
“…NFATc and AP-1 heterodimers form a transcriptional complex that synergistically activates target genes (20)(21)(22). We found that reporter activity of F4 constructs containing a mutant ATF/ CREB site was markedly decreased relative to wild-type F4 constructs ( Supplementary Fig.…”
Section: Atf2 and C-jun Enhance Nfatc-dependent Angptl2 Expression Inmentioning
confidence: 82%
“…The nonconsensus binding site 5Ј-TTAGTCA-3Ј in egl-13, with one nonconsensus half site, 5Ј-TTAG-3Ј, and one consensus half site, 5Ј-TGAC-3Ј, may favor binding by a Fos/Jun heterodimer (Ramirez-Carrozzi and Kerppola, 2003). Thus, we tested if FOS-1 and JUN-1 together can bind egl-13 URS in vitro.…”
Section: Fos-1 Specifically Binds In Vitro To Egl-13 Urs As a Heterodmentioning
confidence: 99%